COMPARATIVE TRANSLATORY ON THE SYARIAH AND CONVENTIONAL CONTRACT LEGAL SYSTEMS: INDONESIA'S PERSPECTIVES - Susilowardani; Desi Syamsiah, Asri Agustiwi, Dara Pustika Sukma (INTELIGENSIA MEDIA, 2024)
The study aims to conduct a comparative study of the Shariah and conventional contractual legal systems from an Indonesian perspective. In the context of Indonesia, the Sharia law system is based on the principles of Islamic Shariah, while the conventional legal system is founded on the general principles that apply in the country. The method of research carried out is the study of literature by searching for literature that fits the context of research. The research shows that the Sharia law system emphasizes the principles of Shariah, such as the prohibition of interests and charges, and encourages dispute settlement through arbitration and arbitrations mechanisms. On the other hand, conventional legal systems are more flexible and focus on commercial aspects in the execution of contracts, using common dispute resolution mechanism, like courts, mediation, or negotiations. Although the Sharia law system provides special legal protection for the parties involved in a Sharia contract, the conventional legal system provides general legal protection to all parties engaged in a contract.